Homogeneous anisotropic cosmological models with variable gravitational and cosmological "Constants" - Singh T.; Agrawal A.K. (My University, 2025)
The Einstein field equations with perfect fluid source and variable Λ and G for Bianchi-type universes are studied under the assumption of a power-law time variation of the expansion factor, achieved via a suitable power-law assumption for the Hubble parameter suggested by M. S. Berman. All the models have a power-law variation of pressure and density and are singular at the epoch t=0. The variation of G(t) as 1 /t and Λ(t) as 1 /t2 is consistent with these models. © 1993 Plenum Publishing Corporation.